Pausanias and Hadrian, Mantineia and Bithynion - Roy, James (Histos, 2016)
Building on the work of Pretzler, this article seeks to refine and strengthen the view that the version of Mantinean history given by Pausanias is derived from the Mantinean elite of his day, and was accepted and reinforced by Hadrian when he founded a cult of Antinoos at Mantinea. But it also introduces the new argument that the tradition making the Mantineans the ancestors of Bithynion, birthplace of Antinoos, was created by Hadrian himself.